Narrative, literacy and other skills : studies in intervention - Veneziano, Edy; Nicolopoulou, Ageliki (Studies in narrative, 2019)
In recent years, narrative skills have been receiving increasing attention from researchers for their relevance in the development of language, literacy and socio-cognitive abilities. This volume brings together studies focusing on two key issues in the development of children's narrative skills. The first part of the Volume addresses the issue of the interrelatedness between narrative skills and literacy, language and socio-cognitive development, as well as of the impact of narrative practices on the promotion of these different skills. The second part of the Volume addresses the issue of how early interactional experiences, particular contextual settings and specific intervention procedures, can help children promote their narrative skills.0The studies span a wide age range, from toddlers to late elementary school children, concern different languages (Dutch, English, French, German, Hebrew and Italian), and consider narrative skills and practices from a rich variety of theoretical and methodological approaches.